Implementasi Metode Fuzzy Analytical Hierarchy Process (FAHP) Pada Sistem Pendukung Keputusan Pemilihan Material Bangunan Berdasarkan Kesesuaian Budget Konsumen Berbasis Website Di Toko Abadi Jaya - Ilivia Ilivia; Elviana Elviana; Mulyadi Tan; Zulfachmi Zulfachmi; Dedy Jauhari (Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2021)
A budget is a financial estimate that is prepared in the form of income and expenses with the intention of making it efficient for a certain period of time. The meaning of budget in Indonesian is a budget. The budget that has been created is not left to chance. It will definitely be compared with actual use to evaluate whether it is appropriate or if there are changes to make the budget more efficient. This is an obstacle for PT. Eternal Jaya. The obstacle to development is the budget problem in purchasing materials. Every construction carried out must make an estimate of the materials used according to the budget. But not all companies can do that. The lack of information about prices and types of material is one of the constraining factors in determining which material to buy according to the budget. The research method used is to use the Fuzzy Analytical Hierarchy Process method to determine materials according to the budget and conduct direct surveys and then interviews. The results of the Implementation of the Fuzzy Analytical Hierarchy Process (FAHP) Method on the Decision Support System for the Selection of Building Materials based on Budget Suitability. Website-based consumers at Toko Abadi Jaya can help Toko Abadi Jaya in selecting materials that fit the budget.